PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Subiantoro, Okky Hendro; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is conducted on manufacturing companies in Indonesia. This research is meant to examine theinfluence of the characteristics of the company to the disclosure of corporate social responsibility. The result ofthis research shows that the firm size does not have any influence to the disclosure of corporate socialresponsibility, leverage does not have any influence to the disclosure of corporate social responsibility,profitability does not have any influence to the disclosure of corporate social responsibility, industrial type(profile) does not have any influence to the disclosure of corporate social responsibility, and managementownership does not have any influence to the disclosure of corporate social responsibility. Meanwhile the size ofthe board of commissioner has an influence to the disclosure of corporate social responsibility.Keywords: Corporate Social Responsibility, characteristics of the company, the Size of the Board ofCommissioner, Management Ownership.